2021
DOI: 10.1088/1741-2552/ac0767
|View full text |Cite
|
Sign up to set email alerts
|

Inter-stimulus phase coherence in steady-state somatosensory evoked potentials and its application in improving the performance of single-channel MI-BCI

Abstract: Objective. With the development of clinical applications of motor imagery-based brain–computer interfaces (MI-BCIs), a single-channel MI-BCI system that can be easily assembled is an attractive goal. However, due to the low quality of the spectral power features in the traditional MI-BCI paradigm, the recognition performance of current single-channel systems is far lower than that of multi-channel systems, impeding their use in clinical applications. Approach. In this study, the subjects’ right and left hands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…To further study the ISPC feature discrepancy between two unilateral foot MI tasks, the 𝑟 coefficient and corresponding topographical maps at different times were compared, as seen in Figure 5(b). As shown in the lower panel of Figure 5, the ISPC revealed a high discrepancy during the MI task period, which agreed with the conclusion of upper-limb [17], but the results of lower-limb were much smaller. The topographical maps of the 𝑟 coefficient spatial distributions showed that the ISPC discrepancies between leftright foot motor intentions mainly focused on the sensorimotor area near the central area, which was consistent with the previous results shown in Figure 4(c).…”
Section: A Erd and Sssep Featuressupporting
confidence: 84%
See 3 more Smart Citations
“…To further study the ISPC feature discrepancy between two unilateral foot MI tasks, the 𝑟 coefficient and corresponding topographical maps at different times were compared, as seen in Figure 5(b). As shown in the lower panel of Figure 5, the ISPC revealed a high discrepancy during the MI task period, which agreed with the conclusion of upper-limb [17], but the results of lower-limb were much smaller. The topographical maps of the 𝑟 coefficient spatial distributions showed that the ISPC discrepancies between leftright foot motor intentions mainly focused on the sensorimotor area near the central area, which was consistent with the previous results shown in Figure 4(c).…”
Section: A Erd and Sssep Featuressupporting
confidence: 84%
“…As a modulation signal influenced by MI, the phase synchronization of the SSSEP may also change during the MI task periods. Here, we employed interstimulus phase coherence (ISPC) to measure phase synchronization variations under somatosensory stimulation [17]. Assuming that 𝑓 is the SSSEP frequency, the original EEG 𝑆(𝑡) is first filtered to the [𝑓 − 0.5, 𝑓 + 0.5] SSSEP band, and then the filtered signal 𝑆 (𝑡) is segmented by a sliding window, which moves 1/𝑓 seconds between two adjacent sliding windows.…”
Section: Erd and Sssep Feature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that, to a lesser extend, one publication also uses phrase information [42]. The Inter-Stimulus Phase Coherence is computed using the Hilbert transform and the analytic signal form of the EEG.…”
Section: 42mentioning
confidence: 99%